2017
DOI: 10.1155/2017/2163053
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Systematic Review of Ginsenoside‐Rg1 in Experimental Parkinson’s Disease

Abstract: To date, no drug has been proven to be neuroprotective or disease-modifying for Parkinson's disease (PD) in clinical trials. Here, we aimed to assess preclinical evidence of Ginsenosides-Rg1 (G-Rg1), a potential neuroprotectant, for experimental PD and its possible mechanisms. Eligible studies were identified by searching six electronic databases from their inception to August 2016. Twenty-five eligible studies involving 516 animals were identified. The quality score of these studies ranged from 3 to 7. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Taken together, these findings indicated that ginseng exhibits its neuroprotective properties and improves is could be due to the presence of bioactive compound ginsenosides in ginseng. Several studies have reported on the neuroprotective effect of ginsenosides, particularly ginsenosides Rg1, in various neurodegeneration models [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…Taken together, these findings indicated that ginseng exhibits its neuroprotective properties and improves is could be due to the presence of bioactive compound ginsenosides in ginseng. Several studies have reported on the neuroprotective effect of ginsenosides, particularly ginsenosides Rg1, in various neurodegeneration models [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…The plant has been used in traditional Chinese medicine for a more than 2000 years as a tonic for fatigue, weakness and aging (Wang et al, 2010 ). Some constituents of this plant, such as ginsenosides Rg1 and Rg3 (Figure 5 ) and ginseng polysaccharides, have been investigated for their therapeutic potential (Yin et al, 2013 ; Song et al, 2017 ; Sun et al, 2017 ). The neuroprotective effect of ginseng is mainly attributed to the 20( S )-ginsenoside Rg3 (Figure 5 ), which has a steroidal backbone structure with carbohydrate part and aliphatic side chain (Yang et al, 2009 ).…”
Section: Selected Prominent Medicinal Plants and Plant Genera Used Fomentioning
confidence: 99%
“…These data indicate that the G-Rg1 content is clearly higher in P. notoginseng than in P. ginseng and that the stems and leaves seem to have more value. Additionally, G-Rg1 is regarded as one of the main bioactive compounds responsible for the pharmaceutical actions of ginseng, which show little toxicity, and some evidence has shown that its pharmacological effects are remarkable in that they include neurotrophic and neuroprotective effects on the central nervous system [20,21,22,23,24,25,26,27,28,29]. Most importantly, as a tetracyclic triterpenoid (Figure 1E) found in natural medicinal plants, G-Rg1 could promote hippocampal neurogenesis, improve neuroplasticity, enhance learning and memory, exert anti-aging [30] and antifatigue effects, and regulate immunity and antitumor activity [31,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%